Fecal Calprotectin: A Reliable Predictor of Mucosal Healing after Treatment for Active Ulcerative Colitis - Vendel Kristensen; Arne Røseth; Tahir Ahmad; Viggo Skar; Bjørn Moum (Gastroenterology Research and Practice)
Objectives. Mucosal healing has become the new goal of treatment in ulcerative colitis. Fecal calprotectin has been demonstrated to differentiate between mucosal inflammation and mucosal healing. With this project, we investigated whether a reduction in f-calprotectin to <250 μg/g after medical treatment for active ulcerative colitis could predict mucosal healing. Material and Methods. After a baseline colonoscopy, 20 patients with active ulcerative colitis were followed with consecutive fecal calprotectin monthly until two measurements of fecal calprotectin < 250 μg/g or a maximum follow-up of 12 months. A flexible sigmoidoscopy was then performed and Mayo endoscopic subscore was used to evaluate degree of inflammation. Simple Clinical Colitis Activity Index was used for evaluation of clinical disease activity. Results. A total of 16 patients achieved fecal calprotectin < 250 μg/g during follow-up, and all 16 patients had endoscopic mucosal healing (Mayo endoscopic subscore of ≤1) on the second endoscopy. The remaining four patients had persistently high f-calprotectin levels before the second endoscopy with Mayo endoscopic subscore corresponding to endoscopic mucosal healing in three out of four patients. Conclusions. Fecal calprotectin <250 μg/g after medical treatment for active ulcerative colitis is a reliable marker of endoscopic mucosal healing.